Dietary Iron Enhances Colonic Inflammation and IL-6/IL-11-Stat3 Signaling Promoting Colonic Tumor Development in Mice - Chua, Anita C. G. (Public Library of Science, 2013)
Chronic intestinal inflammation and high dietary iron are associated with colorectal cancer development. The role of Stat3 activation in iron-induced colonic inflammation and tumorigenesis was investigated in a mouse model of inflammation-associated colorectal cancer. Mice, fed either an iron-supplemented or control diet, were treated with azoxymethane and dextran sodium sulfate (DSS). Intestinal inflammation and tumor development were assessed by endoscopy and histology, gene expression by real-time PCR, Stat3 phosphorylation by immunoblot, cytokines by ELISA and apoptosis by TUNEL assay. Colonic inflammation was more severe in mice fed an iron-supplemented compared with a control diet one week post-DSS treatment, with enhanced colonic IL-6 and IL-11 release and Stat3 phosphorylation. Both IL-6 and ferritin, the iron storage protein, co-localized with macrophages suggesting iron may act directly on IL-6 producing-macrophages. Iron increased DSS-induced colonic epithelial cell proliferation and apoptosis consistent with enhanced mucosal damage. DSS-treated mice developed anemia that was not alleviated by dietary iron supplementation. Six weeks post-DSS treatment, iron-supplemented mice developed more and larger colonic tumors compared with control mice. Intratumoral IL-6 and IL-11 expression increased in DSS-treated mice and IL-6, and possibly IL-11, were enhanced by dietary iron. Gene expression of iron importers, divalent metal transporter 1 and transferrin receptor 1, increased and iron exporter, ferroportin, decreased in colonic tumors suggesting increased iron uptake. Dietary iron and colonic inflammation synergistically activated colonic IL-6/IL-11-Stat3 signaling promoting tumorigenesis. Oral iron therapy may be detrimental in inflammatory bowel disease since it may exacerbate colonic inflammation and increase colorectal cancer risk.